Public investment and corporate productivity in Croatia - Sanja Borkovic; Peter Tabak (Public Sector Economics, 2018)

(untitled)
Motivated by the weak productivity growth, low investments and unfavourable demographic dynamics in Croatia, the paper investigates the relationship between public investment and the productivity of Croatian firms. Our results suggest that government investments in general have a significant and positive effect on total factor productivity (TFP) at firm level. The positive effect can be established only for private sector companies though, while state-owned enterprises do not seem to benefit significantly from these investments. The latter may be due to the relatively small sample of public firms. However, not every type of public investment is significant for Croatian companies. While investments in transport and R&D tend to enhance productivity throughout the economy, investments in human capital work only at the sectoral level by supporting the productivity of enterprises operating in tourism. Sector-level analysis confirms that all the sectors examined benefit from public investment in transport but also reveals that investments in R&D tend to increase the productivity of manufacturing companies only.